Evaluation of the Accuracy of a Video and AI Solution to Measure Lower Leg and Foot Volume - Chausiaux O (Dove Medical Press, 2021)
Oriane Chausiaux,1 Gareth Williams,1 Michał Nieznański,1 Adem Bagdu,2 Philip Downer,1 Melanie Keyser,1 Shamus Husheer1 1Heartfelt Technologies Ltd, Cambridge, UK; 2Warwick Medical School, University of Warwick, Coventry, UKCorrespondence: Oriane Chausiaux Email oriane@hftech.orgBackground and Objectives: Peripheral edema, change in foot volume, is a marker of congestion which is regularly assessed in routine clinical care. A novel video and Artificial Intelligence (AI)-based solution used to measure anatomical parameters, including volume and foot length, Heartfelt HF-1, is compared to the laboratory gold standard (water displacement) and a medical disposable measuring tape.Design, Setting, Participants, and Measurements: 58 healthy volunteers were measured with the Heartfelt device; 22 were also measured with the water displacement method and 19 with the medical tape. Bland–Altman analysis was performed for both volumes and foot lengths. Left/right foot differences provided covariance-corrected standard error of measurement (ccSEM) and minimum detectable difference (MDD) for each measurement method.Results: Heartfelt device measured volumes displayed excellent correlation to the gold standard (water displacement), with Bland–Altman bias of +32mL ± 81mL (1 std.dev). Clinically important change in foot volume is approximately 13%. Water displacement yielded ccSEM of ± 32.1mL and MDD of 90mL (6.7% of average foot volume), while the Heartfelt device measurements yielded ccSEM of ± 12.6mL and MDD of 35.3mL (2.6% of average foot volume). The majority of differences were attributable to manual positioning of the patient foot in the waterbath.Conclusion: This study finds that in clinical and non-clinical settings, the Heartfelt device measures foot volume and length more precisely than either the water displacement technique or manual foot length measurements using a medical disposable tape, while having an excellent agreement with these methods.Keywords: AI, peripheral edema, congestion, -medical device, heart failure, lymphedema, renal disease